2018
DOI: 10.5897/jvmah2018.0670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine of schistosomosis in and around Nekemte, East Wollega zone, Western Ethiopia

Abstract: A cross-sectional study was conducted from March 2016 to May 2016 at Guto Gida District, Nekemte, Ethiopia to determine the prevalence of bovine schistosomosis. Simple random sampling method was used to select the study animals and sedimentation technique was applied for finding Schistosoma eggs from fresh fecal samples. Out of 384 fecal samples examined, 22 were found positive indicating an overall prevalence of 5.7% schistosomosis in the study area. The prevalence of bovine schistosomosis was higher in Jiren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…To evaluate the prevalence rate of bovine schistosomiasis in Ethiopia, 7,378 cattle were used in this case. The prevalence of bovine schistosomiasis ranged between 5.8 and 60.4% [ 20 , 21 ]. The detailed characteristics of the included studies are presented in ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the prevalence rate of bovine schistosomiasis in Ethiopia, 7,378 cattle were used in this case. The prevalence of bovine schistosomiasis ranged between 5.8 and 60.4% [ 20 , 21 ]. The detailed characteristics of the included studies are presented in ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the prevalence of schistosomiasis in cattle was higher in poor body condition animals [ 13 , 22 , 23 , 26 , 28 , 33 ], followed by medium body condition animals [ 10 ] ( Table 4 ). On the other hand, [ 20 , 30 ] found no significant association between the prevalence of schistosomisis and the body condition of the animals which was 24% (95% CI; 22–26%; p = 0.79) and 57% (95%CI 38–85%; p = 0.073), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Using snails as an intermediary host, schistosomiasis is disseminated; the immature infectious form enters through the host's body and can potentially infect cattle by drinking water. 11 It is frequently found in Ethiopia's central, southwestern, eastern, and northwestern regions. 12 In Ethiopia; distinct Bulinus species serve as intermediary hosts, as documented in various parts of Ethiopia, such as Gondar, Tigray, Gojjam, Shewa, Arsi, Harrarge, and Wollo.…”
Section: Introductionmentioning
confidence: 99%
“…17 These epidemiological investigations provide evidence of the regular occurrence of diseases, particularly in areas with stagnant water and swampy open grazing zones. In Ethiopia, the occurrence of animal schistosomiasis caused by S. bovis has been documented, with prevalence rates ranging from 5.7% to 23% in ruminants according to studies conducted by 7,11,18 reported a high prevalence of schistosomiasis of 60% in the southern part of Ethiopia, while 13 reported a prevalence of 17% in the northwestern region.…”
Section: Introductionmentioning
confidence: 99%